Experimental evaluation of a Chinese sulfur-containing lean iron ore as the oxygen carrier for chemical-looping combustion - Wang, Xiaojia; Liu, Hao; Jin, Baosheng; Zhao, Jie; Sun, Chenggong; Snape, Colin E. (American Chemical Society, 2016)
A series of chemical-looping combustion (CLC) tests were conducted in a thermogravimetric analysis (TGA) reactor to investigate the potential of a Chinese sulfur-containing lean iron ore as the oxygen carrier. Two main products of solidfuel pyrolysis and gasification, namely, CH4 and CO, were selected as the reducing gases. Consecutive reduction−oxidation cycles were first carried out in the TGA reactor to evaluate the cyclic stability and agglomeration tendency of the oxygen carrier. The effects of the temperature, fuel gas concentration, and reaction gas composition on the reduction reaction were further investigated. Increasing the reaction temperature or fuel gas concentration enhanced the reduction rate and reaction degree of the oxygen carrier. Meanwhile, CO showed much higher reduction reactivity than CH4. A comparison of the rate index of the iron ore used with those of high-grade minerals indicated that the iron ore had adequate reactivity for its application in solid-fuel CLC technology. The side reaction of carbon deposition was also discussed. Finally, the shrinking-core model with chemical reaction control was adopted to determine the chemical kinetics.